Primary bone tumours and tumour-like lesions in children in Zaria, Nigeria - Sani Malami; Hezekiah Isah; Enoch Afolayan; Mohammed Abdullahi (Wolters Kluwer Medknow Publications, 2010)
Background: Studies on bone neoplasms are generally scanty globally and more so in children. Primary bone tumours and tumour-like lesions in children have not been reported from Zaria. Objective: To determine the relative frequencies, sex and age distributions, and anatomical sites of occurrence of primary bone tumours and tumour-like lesions in children in Zaria. Materials and Methods: A retrospective review of histopathology reports of 40 children with bone tumours and tumour-like lesions in 11 years of age. Results: Benign tumours accounted for 12 (30%) of the 40 tumours reviewed (osteoma 2.5%, osterochondroma 22.5%, fibroma 5%); while malignant tumours occurred in 19 (47.5%) (osteosarcoma 5%, Burkitt′s lymphoma 37.5%, diffuse lympholastic lymphoma 5%). Tumour-like lesions accounted for 9 (22.5%), all fibrous dysplasia. Out of 40 tumours, 23 (57.5%) occurred in males and 17 (422.5%) in females. The majority of tumours, 45% occurred in the age group of 10-15 years, followed by 15 (37.5) occurring in the 5−9 years age range. The most common malignany was Burkitt′s lymphoma 15 (37.5%). Maxilla was the most common site for malignant (30%) and benign tumours (12.5%). Conclusion: This study has shown that, primary bone tumours are relatively uncommon in children in our setting.